A Semiotic Reading to the Rhetorical Signification in Abbassid Pursuit Poems up to the 4th Century AH: A semiotic study - Hamadan, Sajed; Iskandar, Yousif (Al-Adab Journal, 2025)
Hunting and pursuit trips arose for reasons such as: self-defence, food pursuit, or entertainment. If we attribute it to self-defence or seeking food, we must trace its origins back to ancient times as old as man himself. As for what is related to entertainment and pleasure, it resulted from man’s culture and his social and psychological stability which gave birth to his love of practicing pursuit far from motives. The picture of pursuit constitutes a painting within the multi-themed pre-Islamic poem, and this was the case until the end of the Ummayad era and the beginning of the Abbasid one when it witnessed its independence in Arajees known as Pursuit Poems to be a new art that joins the art of Arabic poetry and a special characteristic for the Abbasid era which witnessed luxury and wealth for the private and the public. That enabled them to spend on this art for the sake of pleasure and entertainment. This topic consists of studying the scenes of hunting and pursuit documented by the Abbasid poet, analyzing them and exploiting their rhetorical connotation represented by thematic images and roles.